The immunological implications of nanocomposite drug delivery systems - Nikandish, Mehrasa; Rezazadeh Moghaddam, Bahram; Chinaveh, Melika; Ziaeijazi, Aynaz; Akhvlediani, Leila; Gujabidze, Ana (Journal of Composites and Compounds, 2025)
This review discusses recent advances in nanocomposite applications, with a particular concentrate on their progress as drug delivery systems. It explores the intrinsic properties of nanocomposites that effect their interaction with the immune system and potential in vivo toxicity. It also includes the immune system's interaction with nanomaterials, immunological responses provoked by nanocomposite systems, and the factors that impact immune reactions such as size, shape, surface properties, composition, and biodegradability. The review also discusses surface modifications and targeting ligands that can optimize nanocomposite performance. Through understanding nano-bio interfaces technology, researchers can design bio-effective nanomaterials that open new possibilities for biomedical applications, especially as targeted and safe drug delivery platforms.